Uncommon RB1 somatic mutations in a unilateral retinoblastoma patient - Ottaviani, Daniela (2015)
Retinoblastoma (RB) is the most common primary intraocular malignancy in children. Somatic inactivation of both alleles of the RB1 tumor suppressor gene in a developing retina is a crucial event in the initiation of tumorigenesis in most cases of isolated unilateral retinoblastoma. We analyzed the DNA from tumor tissue and peripheral blood of a unilateral retinoblastoma patient to determine the RB1 mutation status and to provide an accurate genetic counseling. A comprehensive approach, based on our previous experience, was used to identify the causative RB1 mutations. Screening for RB1 mutations was performed by PCR direct sequencing, multiplex ligation-dependent probe amplification (MLPA) and Real Time-PCR analyses. Three different mutations were identified in the tumor DNA, which were absent in blood DNA. The somatic origin of these mutations was vital to rule out the heritable condition in this patient.